Difference of levels in emotional-social intelligence among practicing and non-practicing catholics students of a private school - Anchorena O., Sandra (2014)
This study compared the difference in levels of emotional-social intelligence among practicing and non-practicing catholic students of a private catholic school in the district of Surco in Lima. The sample of 148 adolescents of fourth and fifth secondary grade of both sexes aged 14 to 17 years old, it was divided in two groups according to frequency of Mass attendance. The Bar-On Emotional Quotient Inventory Young Version (EQ-i:YV) adapted to the Peruvian population, it was used. Practicing catholic students scored better on the test and in all its dimensions or sub-scales. The Student t test showed significant differences in emotional- social intelligence and in two of its dimensions: interpersonal and stress management, where practicing catholic students outscored the non-practicing catholic students.